2022
DOI: 10.1007/s40615-022-01260-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Risk and Protective Factors of Nigerian Male Asylum Seekers Hosted in Southern Italy: a Culturally Sensitive Quantitative Investigation

Abstract: This study provides a culturally sensitive quantitative investigation aimed at assessing the post-traumatic symptomatology, post-migratory difficulties, and resilience of 36 Nigerian male asylum seekers hosted in the province of Caserta, South Italy. A survey composed by the Harvard Trauma Questionnaire-Revised (HTQ-R), the Post-Migratory Checklist (PLMD), and the Connor-Davidson Resilience Scale (CD-RISC) was administered to participants. Descriptive and correlation analyses were made in order to describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 61 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Research with professionals working with migrants in Italy showed that operators embracing an idealized professional profile could be satisfied by their work as well as being unable to recognize physical and mental fatigue [78]. Moreover, in the field of forced migration, not only personal resources but also all relational and contextual variables such as the work climate, the surviving experience of resistance in intersubjective terms might assume an important role in preserving the professional quality of life of the operators [3,14,79]. In any case, the relationship between secondary traumatic stress and compassion satisfaction remains an interesting area which needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Research with professionals working with migrants in Italy showed that operators embracing an idealized professional profile could be satisfied by their work as well as being unable to recognize physical and mental fatigue [78]. Moreover, in the field of forced migration, not only personal resources but also all relational and contextual variables such as the work climate, the surviving experience of resistance in intersubjective terms might assume an important role in preserving the professional quality of life of the operators [3,14,79]. In any case, the relationship between secondary traumatic stress and compassion satisfaction remains an interesting area which needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The bonds seemed to waver, as did the spaces of thought. The operators who experienced the extent of the emotional impact, as often happens in these clinical contexts with a high degree of complexity, a real vicarious trauma (Margherita et al, 2020;Tessitore et al, 2022Tessitore et al, , 2023aTessitore et al, , 2023bTroisi et al, 2021) felt the difficulty in maintaining an identity continuity of the project. In a subsequent group meeting, which brought together all the institutional operators, we returned to this moment, through a different state of mind.…”
Section: Dreaming Of Woundsmentioning
confidence: 99%
“…In fact, migration has been described as an experience of re-birth that re-proposes the infantile condition of child inermity (the Freudian hilflossigkeit) (Grinberg & Grinberg, 1989). In this sense, the challenges faced by the migrant related to learning the language as well as the acculturation processes can be compared to those of the infans and contain a strong traumatic potentiality, which might end up generating a deep fracture of cultural identity (Margherita & Tessitore, 2019;Tessitore et al, 2023aTessitore et al, , 2023b.…”
mentioning
confidence: 99%